Analysis of consumer behavior in a small size market entity: case study for Vlora District, Albania - Kushta, Elmira; Prenga, Dode; Memaj, Fatmir (International Journal of Scientific Research and Management (IJSRM), 2018)
In standard econometric application all variables are analyzed statistically before being used in mathematical models. In this framework we considered non-stationary distribution as an starting procedure on the study of consumer behavior in a local market area whereof non-homogeneity of buyers and small size effect could be present. By evaluation of the degree of non-stationary of the actual state for particular variable as observed, we hope to be able to estimate and interpret the model outcomes. Assuming the non-stationary of variables as indicator of the overall stet itself, we argue that the state where observation were made is non-stationary too, and for that reason, models are expected to not fit well. In the other hand, by dropping the significance level in model fitting process we expect to count for this instability whereas the model remains valid. Herewith, the logistic model for consumer behavior in our system is applied and calculated using significance level 0.85-0.90. Under such limiting constraint assumption we identified the variables that mostly affected the proportion between expense categories and the characteristics of the expenses that mostly describe the market consumer behavior in the unity studied. We hope that methodically this procedure could be helpful for other similar market or socio-metric study as well.